Paradigm for the Recruitment of Supreme Court Judges by the House of Representatives is Part of Constitutional Political Intervention - Ali Murtadho, Nazhif (Journal of Law, Politic and Humanities, 2024)
The pattern of recruitment of Supreme Court justices which is constitutionally regulated in Article 24A paragraph (3) requires that the nomination of Supreme Court judges is carried out through a nomination mechanism that has been carried out by the Judicial Commission to be approved by the DPR and determined by the President as part of the check and balance concept. However, in such a mechanism it actually confronts a paradigm in which the concept of checks and balances that is presented actually intersects with the concept of independence from the judicial power itself. So by using the literature study or library research method, a conception is obtained that so far the concept of checks and balances has not been placed in the right realm. So that it often creates a problem that intersects one authority with another, including in the realm of the mechanism for the recruitment of Supreme Court justices. So it is important to understand how the conception of Article 24A paragraph (3) is the legal basis for the pattern of recruitment of Supreme Court justices. As well as occupying the concept of the independence of the Judicial Commission in an effort to create accountable supreme justices.